A case–control study of occupational sunlight exposure and renal cancer risk. Issue 7 (14th November 2015) - Karami, Sara; Colt, Joanne S.; Stewart, Patricia A.; Schwartz, Kendra; Davis, Faith G.; Ruterbusch, Julie J.; Chow, Wong‐Ho; Wacholder, Sholom; Graubard, Barry I.; Purdue, Mark P.; Moore, Lee E.
Abstract : Epidemiological evidence of a relationship between vitamin D and kidney cancer risk has been inconsistent despite experimental data indicating that vitamin D and its metabolites may inhibit carcinogenesis. Previously we reported an inverse association between renal cell carcinoma (RCC) risk and occupational ultraviolet (UV) exposure among European men. In this study, we examined the association between occupational UV exposure and RCC risk among US residents and investigated whether this association varied by race and sex. Lifetime occupational data for 1, 217 RCC cases and 1, 235 controls in a population‐based case–control study, conducted from 2002 to 2007, were assessed for occupational UV exposure. We evaluated exposure metrics in quartiles based on control exposure levels and calculated associations between RCC risk and occupational UV exposure using unconditional logistic regression adjusted for sex, race, body mass index, smoking, hypertension, center, education, family history of cancer and dietary vitamin D intake. A general pattern of decreasing RCC risk with increasing UV exposure was observed. Cases had significantly lower cumulative occupational UV exposure than controls (fourth quartile vs . first: odds ratio = 0.74 [95% confidence interval = 0.56–0.99], p ‐trend = 0.03). Similar results were observed for other UV exposure metrics. The association with occupational UV exposure was stronger for women than for men, but did not differ by race. Our findings suggest an inverse association between occupational UV exposure and RCC, particularly among women. Given the sex finding discrepancies in this study versus our previous study, additional research is need to clarify whether the protective effects of occupational UV exposure and RCC risk are real. Abstract : What's new? Although evidence from observational studies hints toward a possible role for vitamin D in reducing the risk of renal cell carcinoma (RCC), the most common type of kidney cancer in adults, findings from epidemiological studies have been inconsistent. To shed light on the relationship, the authors of this study examined associations between RCC and occupational sunlight exposure in a US case‐control study. RCC risk was found to decrease as sunlight exposure increased, most notably for women. Moreover, among RCC cases, exposure to sunlight was markedly lower than that of controls. RCC risk did not vary between blacks and whites.